2018
DOI: 10.4172/neuropsychiatry.1000432
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Depression in Religiosity and Cognitive Function among Chinese Muslim Elderly

Abstract: The current study examined the association between religiosity and mild cognitive impairment (MCI), along with the mediating role of depression, in Chinese Muslim elderly sample. 1,347 community Muslims aged 55 years or older were recruited in Ningxia, China. The Mini-Mental State Exam, the Geriatric Depression Scale, and the Duke University Religion Index were administered. Structural equation modeling (SEM) was used to detect the mediation effect. Approximately 21.3% participants reported experiencing mild o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Similarly, previous research has also shown a moderating effect of church attendance on the relationship between depressive symptoms and cognitive function, where higher levels of church attendance appears to have buffered the negative impact of depressive symptoms on cognitive function 83 . A Chinese study using a structural equation modelling (SEM), found that religiosity partly improves cognitive functioning due to its inverse relationship with depression possibly by increasing social networks 84 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous research has also shown a moderating effect of church attendance on the relationship between depressive symptoms and cognitive function, where higher levels of church attendance appears to have buffered the negative impact of depressive symptoms on cognitive function 83 . A Chinese study using a structural equation modelling (SEM), found that religiosity partly improves cognitive functioning due to its inverse relationship with depression possibly by increasing social networks 84 .…”
Section: Discussionmentioning
confidence: 99%
“…Since spirituality increases in importance as a person ages, the present study suggests that supporting the older persons spirituality may be another way to improve their mental and physical health, doing so by accommodating their faiths during various interventions 44 . A higher DUREL score may also correlated with better memory, orientation and language skills, as others have shown 45 . As previous study found that spiritual practice can stimulate and activate the regions of the frontal and temporal lobes of the brain, where the cognitive function was in charged 46 .…”
Section: Discussionmentioning
confidence: 71%
“…Many researchers investigated the relationship between religion and health in people's late life (McFadden, 2005;Koenig et al, 2012;Schuurmans-Stekhoven, 2019). For instance, religious older people tend to have better cognitive function (Sun et al, 2018), decreased depression, improved optimism, self-esteem (McFarland, 2010) and report engaging in more health behaviours (Bakhtiari et al, 2018) relative to older adults who are not religious. However, religion may also have a negative influence on older adults' health.…”
Section: Religion and Health Among Older Adultsmentioning
confidence: 99%